LGBT activism and the making of Europe: A rainbow Europe - Ayoub, Phillip; Paternotte, David (Palgrave Macmillan, 2014)
Europe has long been regarded as a unique place for the promotion and furthering of LGBT rights. This important and compelling study investigates the alleged uniqueness and its ties to a relatively long history of LGBT and queer movements in the region. Contributors argue that LGBT movements were inspired by specific ideas about European democratic values and a responsibility towards human rights, and that they sought to realize these on the ground through activism, often crossing borders to foster a wider movement. In making this argument, they discuss the 'idea of Europe' as it relates to LGBT rights, the history of European LGBT movements, the role of European institutions in adopting LGBT policies, and the construction of European 'others' in this process.
Keywords: LGBTQIA2+; activisme; approches et analyses; cours; discipline; europe; histoire; histoire et politique; identités LGBTQIA2+; justice sociale; militance; mouvements de libération; mouvements lgbtia2+; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sex1183; thématiques

Sexualité - Weeks, Jeffrey; Mendès-Leite, Rommel; Collomb-Boureau, Colette; Millet, Baudoin; Baudry, Samuel (Presses universitaires de Lyon, 2014)
Première traduction française d’un ouvrage de Jeffrey Weeks, ce « manifeste intellectuel » est d’ores et déjà un classique anglo-saxon depuis plus de vingt ans. Dès sa première édition, il s’est imposé comme une introduction de pointe aux débats sur les sexualités, le genre et l’intime. Jeffrey Weeks retrace l’histoire de la sexualité, pensée comme une construction sociale, façonnée et remodelée inlassablement par le contexte dans lequel elle existe et s’exprime : la sexualité n’est ni naturelle ni uniforme, mais culturelle et plurielle. Cette approche pionnière permet de couvrir un large champ d’investigation : les traditions religieuses, les politiques identitaires, la mondialisation, l’impact social du sida, l’influence de la génétique et de la psychanalyse, la lutte des sexes, les nouveaux modèles familiaux... Désormais, dans sa troisième édition (qui fait l’objet de cette traduction), cet essai majeur intègre de nouveaux concepts et enjeux, issus en particulier des mouvements LGBT et des débats sur le mariage homosexuel.
Section: 1 vol. (303 p.) : couv. ill. en coul. ; 18 cm.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques